The Two Peoples: Dostoevsky on the Triumph and Failure of the Russian Revolution - Tatyana V. Kovalevskaya (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2018)
The article considers the Russian revolution within the context of Dostoevsky’s philosophical anthropology. It shows two different worldviews inherent in different social strata of the Russian society, traces their interrelations and interpenetration and their ties with the revolutionary ideology. The article describes the reasons of both emergence and collapse of the revolutionary project in the broad context of the European worldview and Dostoevsky’s insights into those reasons in his various works.